A Filtering Intolerance In Indonesia Through The Cultivation of Bee Mentality: an Islamic Perspective - Ilmi, Muhammad Hafidz; Sa’adah, Nurus (RUSYDIAH: Jurnal Pemikiran Islam, 2023)
Given the numerous cases of intolerance in recent years, it is necessary to examine the root causes of such incidents, particularly in Indonesia. Despite the government's comprehensive efforts through its moderation movement to promote peace amidst diversity, the campaign is perceived as still relying on traditional paradigms, reaching only a portion of the population. Therefore, the purpose of this article is to outline the values of tolerance derived from the bee's mindset and how they can be applied as a strategy to filter out intolerance in Indonesia, based on an Islamic perspective. The research methodology employed in this study is literature review. The findings indicate that bee-like mentalities are considered relevant for filtering out intolerance, as bees consistently strive to maintain harmony, foster mutually beneficial cooperation, cultivate inner peace, and learn from history to avoid future intolerance. The implementation strategy involves developing an attitude of mutual respect and collaboration among religious communities, promoting freedom of worship, recognizing equality, and revitalizing philosophical values in each region.